Pengaruh Kepemimpinan Transformasional Kepala Sekolah, Motivasi Kerja, Dan Kedisiplinan Terhadap Pengembangan Karir Guru SD - Ngadimin Ngadimin; Wuradji Wuradji (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
This study aims to investigate the extent of the effects of principals’ transformational leadership in terms of teachers’ perception, work motivation, and discipline on the career development of elementary school teachers in Godean District, Sleman Regency. This research is a type of non-experimental quantitative approach, The subjects were teachers in the Unit Yandik Godean districts, teachers involved in the study were 173 persons. The descriptive results of the study show that principals’ transformational leadership is in the high category with a mean of 3.44, teachers’ work motivation is 3.46, teachers’ discipline is 3.36, and teachers’ career development is 2.94. The results of the regression analysis show that principals’ transformational leadership has a significant effect of 18,1% (p<0.05) on elementary school teachers’ career development, teachers’ work motivation has a significant effect of 7,9% (p<0.05) on elementary school teachers’ career development, and teachers’ discipline has a significant effect of 8,4% (p<0.05) on elementary school teachers’ career development. The results of the analysis show that principals’ transformational leadership, teachers’ work motivation, and teachers’ discipline as an aggregate have a significant positive effect of 24,8%, indicated by the statistical test showing F = 19,955 (p < 0.05), on the career development of elementary school teachers in Godean District, Sleman Regency, Yogyakarta Special Territory.